1998
DOI: 10.1080/08964289809596389
|View full text |Cite
|
Sign up to set email alerts
|

How Daughters of Women With Breast Cancer Cope With the Threat of the Illness

Abstract: Coping strategies and attitudes toward medical treatment of 45 daughters of women who had had breast cancer were compared with strategies (sense of coherence) and attitudes on a health opinion survey of 51 women with no such family history who were referred to a breast health clinic in northern Israel. The daughters of women with breast cancer ranked lower on sense of coherence than the women with no such history. They also were more actively involved in the medical setting and requested more medical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Contradictory results have been reported concerning the intensity of emotional distress among DBCP 17,18,52 or among relatives of breast cancer patients. 53,54 The consistency of increased emotional distress found in our DBCP may be attributed to the homogeneity of the study group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Contradictory results have been reported concerning the intensity of emotional distress among DBCP 17,18,52 or among relatives of breast cancer patients. 53,54 The consistency of increased emotional distress found in our DBCP may be attributed to the homogeneity of the study group.…”
Section: Discussionmentioning
confidence: 96%
“…14 -16 The familial risk for breast cancer is widely acknowledged, and DBCP have deep feelings of anxiety about their health, in addition to a concern for their sick mothers. 17,18 As a result, DBCP live in a high degree of chronic stress. 18 The association between chronic stress and impaired immune surveillance functions has long been established, 19,20 while the immunosuppressive effect of chronic stress is presumed to be mediated through excess secretion of the stress hormones cortisol and catecholamines.…”
mentioning
confidence: 99%
“…Meanwhile, community nurses should develop effective prevention strategies for women with FDRs with osteoporosis to reduce the perceived barriers to osteoporosis prevention. Finally, participants were not recruited from a disease-specific clinic, as in most studies of cancer patients (Audrain, Schwartz, & Herrera, 2001;Gilbar & Borovik, 1998). In this investigation, participant self-reporting was utilized as the basis for classifying participants with FDRs with osteoporosis or not.…”
Section: Limitationsmentioning
confidence: 99%
“…That is, not only were individuals with positive parent history of various chronic Intergenerational Influences of Diabetes Mellitus 147 diseases more vigilant with respect to testing for the possibility of disease, but they exhibited higher levels of anxiety and depression associated with disease risk (Cohen, 2002;Forsyth & Goetsch, 1997;Gilbar & Borovik, 1998). In the present study, it is likely that patients with positive parent history of DM may have observed expressions of depression and hopelessness in their parents and such symptoms may have further promoted caution with respect to behaviors that might harm glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Norton, Froelicher, Waters, and Carrieri-Kohlman (2003) showed that parental modeling of healthy behaviors was reflected in their children's lifestyle beliefs. Further, healthy individuals with a positive parent history of one or more chronic diseases were found to exhibit more health-protective behaviors and poorer psychological outcomes than controls (Cohen, 2002;Forsyth & Goetsch, 1997;Gilbar & Borovik, 1998).…”
mentioning
confidence: 97%